1987
DOI: 10.1037/0021-9010.72.4.529
|View full text |Cite
|
Sign up to set email alerts
|

Occupational complexity, control, and personal income: Their relation to psychological well-being in men and women.

Abstract: Research on work and well-being indicates that paid employment has beneficial consequences for mental health. In this study, it was hypothesized that higher occupational complexity, control, and personal income would be associated with higher levels of happiness and self-confidence and lower psychological vulnerability. In addition, the possibility was explored that models describing these correlations for employed women (n = 330) might differ from those for employed men (n = 618). Stepwise regression results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
1

Year Published

1991
1991
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 119 publications
(69 citation statements)
references
References 37 publications
5
62
1
1
Order By: Relevance
“…Volume 5-Number 1 (e.g., Adelmann, 1987;Ross & Huber, 1985) because both findings point to the importance of identity and values in the effects work and money have on well-being. Clark and Oswald (1996) found that job satisfaction depends not on absolute pay, but on pay relative to other workers with the same education and job classification.…”
Section: The Contextual Effects Of Incomementioning
confidence: 99%
“…Volume 5-Number 1 (e.g., Adelmann, 1987;Ross & Huber, 1985) because both findings point to the importance of identity and values in the effects work and money have on well-being. Clark and Oswald (1996) found that job satisfaction depends not on absolute pay, but on pay relative to other workers with the same education and job classification.…”
Section: The Contextual Effects Of Incomementioning
confidence: 99%
“…As such, consumer self-confidence reflects subjective evaluations of one's ability to generate positive experiences as a consumer in the marketplace (Adelman 1987). Consumer self-confidence is viewed as a multifaceted secondary disposition that is more closely related to consumer phenomena than are central dispositions such as self-esteem (Lastovicka 1982).…”
Section: Consumer Self-confidence and Related Conceptsmentioning
confidence: 99%
“…Иными словами, уверенность потребителя в том, что принятое решение является правильным, отражает субъективную оценку отдельного лица своей способности добиваться положительных результатов совершаемых поведенческих действий [Adelman, 1987].…”
Section: исследование воспринимаемого риска покупки товаров под собстunclassified